josephautumn5
josephautumn5
22-08-2022
Mathematics
contestada
3(x² - 4y + x) when x = 6 and y = 7
Respuesta :
Аноним
Аноним
22-08-2022
Answer:
42
Step-by-step explanation:
3(6^2-4*7+6)
6^2=36
4*7=28
(36-28+6)=14
3(14)=42
Answer Link
AnjulaReddy
AnjulaReddy
22-08-2022
Given question ,
[tex] 3 (x^{2} - 4y+x)[/tex]
Also , x = 6 and y = 7
Substituting , we get ,
[tex] 3( 6^{2} - 4(7) + 6) [/tex]
=> 3 (36-28 + 6)
=> 3(14)
=> 42
Answer Link
VER TODAS LAS RESPUESTAS ( 15+ )
Otras preguntas
In the straightedge and compass construction of the equilateral triangle below, which o the following reasons can you use to prove that ABC = BCA?
Even though she is thousands of miles from her sister, the narrator laments that _____. they might as well live close by she wishes she would have ignored the f
What do the numbers after the arrows represent
Which term describes an organism that has identical alleles for a trait? homozygous heterozygous dominant recessive
Solve the system by elimination x+3y=5 -x-y=-3
A (blank) is the specific amount of food or drink eaten in a meal or snack
What are some examples of human service careers
Determine which answer choice accurately describes the combination of clauses in this sentence (16) from the passage. A) The sentence contains two dependent
I need help ASAP! Class ends at 11:00 20 points !!
What role did Eli Whitney's cotton gin have on Upcountry and Lowcountry politics?